Social status representation in senior high school students in a private school in Metropolitan Lima - García, Fernando (2020)
DOI: 10.26439/persona2020.n023(1).4835 Social status plays a central role in teenage school life. This qualitative study aims to examine the representations of school social status among 10 senior private high school students (M = 15,89, DE = 0,33) in Lima. Focus group and in-depth interviews were conducted. Results evidence both dominance and prestige are effective strategies to gain status at school. Dominant students show aggressive behaviors, physical strength, and are associated with drug use among their peers. Prestigious students’ traits are academic achievement, prosocial behavior, and sport success. Non-heterosexual identity and mental illness negatively affect social status in high school. Relations between these factors and their possible implications are discussed.